Edukasi Ketidaknyamanan pada Ibu Hamil Trimester I di Posyandu Dasan Suman Pringgarata - Fadila, Haerunisa; Natalia, Omi (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Pregnancy is a natural and physiological process. Every woman who has healthy reproductive organs, has menstruated, and has had sexual intercourse with a healthy man is likely to get pregnant. The gestation period starts from conception to birth with a duration of 280 days or 40 weeks calculated from the first day of the last menstruation (Nugrawati & Amriani 2021). The maternal mortality rate (IMR) in 2023 in West Nusa Tenggara has increased from the previous year. Where in 2022 there were 20 maternal deaths or 106/100,000 live births and in 2023 it increased to 25 cases or 143.7/100,000 live births. The main cause of the still high number of cases is the lack of infrastructure support, one of which is the KIA book which is used as a promotional and educational media, the lack of competence of health workers, the integrated ANC team is not yet optimal and the integrated referral system is not yet optimal, all of which have been assisted in accordance with the applicable standard operating procedures (SOP) (Dikes NTB, 2023). The purpose of this community service activity is to increase the knowledge of mothers and families about the discomfort of pregnant women in the first trimester. The methods used are counseling and Q&A. The implementation of this activity took place on October 21, 2024 at Mr. S house, counseling was carried out for about 1 hour starting at 09.00 WITA to 10.00 WITA, followed by a physical examination of pregnant women. The means used in providing counseling about the discomfort of pregnant women in the first trimester were leaflets. The results of this activity showed that most respondents had positive traits due to several factors, one of which was knowledge so that it could influence a person's attitude. Sufficient sources of information and a desire to find out so that respondents could have a positive attitude. According to the author, if the respondent's education level is high, it can make it easier for the respondent to receive various information and have an open mind. Good knowledge can reflect a positive attitude. However, even though most respondents have less knowledge, respondents support it by being positive.